2015
DOI: 10.1021/acsami.5b10171
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Bactericidal Activity of Silver Thin Films Deposited via Aerosol-Assisted Chemical Vapor Deposition

Abstract: Silver thin films were deposited on SiO2-barrier-coated float glass, fluorine-doped tin oxide (FTO) glass, Activ glass, and TiO2-coated float glass via AACVD using silver nitrate at 350 °C. The films were annealed at 600 °C and analyzed by X-ray powder diffraction, X-ray photoelectron spectroscopy, UV/vis/near-IR spectroscopy, and scanning electron microscopy. All the films were crystalline, and the silver was present in its elemental form and of nanometer dimension. The antibacterial activity of these samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 39 publications
2
22
0
Order By: Relevance
“…The images indicate fibrous surfaces decorated with AgNP agglomerates of polydisperse distributions in shape and diameter, attached to rGO sheets [90,91]. It is important to note that particles observed on the textile surface via SEM comprise a collection of Ag crystallites and, thus, are much larger than the crystallite sizes estimated by the Scherrer equation [92]. The primarily spherical agglomerations observed in this case are also reflected in the UV-Vis data where there is no observable lateral plasmon shift signal.…”
Section: Nanoparticle-impregnated Polyviscose Substrate Synthesismentioning
confidence: 66%
“…The images indicate fibrous surfaces decorated with AgNP agglomerates of polydisperse distributions in shape and diameter, attached to rGO sheets [90,91]. It is important to note that particles observed on the textile surface via SEM comprise a collection of Ag crystallites and, thus, are much larger than the crystallite sizes estimated by the Scherrer equation [92]. The primarily spherical agglomerations observed in this case are also reflected in the UV-Vis data where there is no observable lateral plasmon shift signal.…”
Section: Nanoparticle-impregnated Polyviscose Substrate Synthesismentioning
confidence: 66%
“…The XRD pattern of Ag/TNTs powder still appears as characteristic peaks of anatase and rutile phases. Besides, Figure 4(b) shows that these observations at 38.2 and 44.4 have represented (111) and (200) planes of the face-centred phase of silver metal [11,16]. These results demonstrated that the Ag NPs existed within the TNTs.…”
Section: X-ray Diffraction Pattern Analysismentioning
confidence: 72%
“…The results of the Ag3d XPS ( Figure 5(d)) have the following spotlight: first, the sample had more common smaller peaks inside the two top large spectra. After using Gaussian fit to analyse the XPS spectra of Ag 3d, there is appearance of peaks at 367.5, 368.6, 371.8, and 375 eV with binding energy positions corresponding to Ag + 3d 5/2 , Ag 0 3d 5/2 , Ag + 3d 3/2 and Ag 0 3d 3/2 , respectively [16,31]. This shows that there is an existence of two states of silver including Ag + and Ag 0 .…”
Section: X-ray Diffraction Pattern Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Within this context, silver is widely recognised and employed as a bio-responsive plasmonic material. [32][33][34] The bactericidal activity of silver seems to be linked to the strong electrostatic adhesion between the negatively charged bacterial outer membrane and the positively charged silver ions, followed by efficient Ag + uptake inside the bacterial cells. [35][36][37] We have preliminarily determined that this might lead to a modication of Ag charge carrier density and shi of the plasmon resonance upon E. coli/Ag interaction.…”
Section: Introductionmentioning
confidence: 99%